2017
DOI: 10.1093/dote/dow033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of definitive chemoradiotherapy using carboplatin and paclitaxel in esophageal cancer

Abstract: Patients with nonmetastatic esophageal cancer not suitable for surgery can be treated with definitive chemoradiotherapy with curative intent. The purpose of this retrospective study is to evaluate the clinical outcomes of definitive chemoradiotherapy using carboplatin and paclitaxel. Medical records were reviewed of patients treated for nonmetastatic squamous cell or adenocarcinoma of the esophagus between January 2009 and December 2013 in two collaborating institutes. Treatment consisted of external beam radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The ratio of local/regional failure and persistence of disease after 2 years in both the high-dose and standarddose arms was more than 50% in RTOG 94-05 [5]. In the present study, the locoregional control rate was 64.3% after 3 years and seemed to be similar to the studies using TC [11,30] but higher than that found in previous studies of PF. Furthermore, the initial failure pattern was so different that there were fewer patients with persistent tumors in our study.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The ratio of local/regional failure and persistence of disease after 2 years in both the high-dose and standarddose arms was more than 50% in RTOG 94-05 [5]. In the present study, the locoregional control rate was 64.3% after 3 years and seemed to be similar to the studies using TC [11,30] but higher than that found in previous studies of PF. Furthermore, the initial failure pattern was so different that there were fewer patients with persistent tumors in our study.…”
Section: Discussionsupporting
confidence: 68%
“…Our results showed that the tumor response rate was 80.8%; the median OS and PFS time were 18.2 months and 11.5 months, and the 3-year OS and PFS were 36.4 and 31.5%, respectively. These results were more promising than previous similar studies of PF and TC-based CRT [9][10][11]18]. However, without a prospective randomized comparison, we can't conclude DP regimen is superior to than PF or TC regimen for locally advanced and recurrent esophageal SCC.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The extremely lethal disease has an overall 5-year survival rate of only 18.8% due to the high rate of late-stage diagnoses and lack of effective therapeutic regimens [ 2 ]. Currently, standard-of-care treatment recommendations for locally advanced esophageal cancer include neoadjuvant chemoradiotherapy followed by surgery, demonstrating only minimal benefit with regard to prognosis [ 3 , 4 ]. Therefore, significant advancements in screening strategies, risk stratification, and novel therapeutics are urgently needed to improve care and prognosis for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with esophageal carcinoma mainly present with dysphagia; however, to our knowledge limited data is available regarding its relief. In a previous study, patients receiving fluorouracil and cisplatin showed improvement from baseline to week 15 (37.6 versus 29.9, p=0.047) [25].Another retrospective study that included patients (N=66) with esophageal carcinoma and treated with chemoradiotherapy (carboplatin and paclitaxel) demonstrated that around 70% of patients had relief of dysphagia [26]. In the present study, dysphasia relief was achieved in 64% and 48% of patients from chemo-radiotherapy and radiotherapy alone group, respectively.…”
Section: Discussionmentioning
confidence: 92%